Report On Toys City Sdn Bhd about operation management/ Farid Wahidi Omar, Ahmad Fuad Abdul Salim and Mohd Azwan Abdullah. - Omar, Farid Wahidi; Abdul Salim, Ahmad Fuad; Abdullah, Mohd Azwan (2006)
Toy City Sdn. Bhd. is a private company which offers services, advises and remote control car products for its customers' satisfaction which comes in a complete package. An initial package can be expanded by adding on more functions to suit customers' need* Its products are easy to use and are made to fulfill customer's satisfaction. Furthermore, this remote control car product is cost effective and comes with easy upgrade paths. In addition, this product is a Malaysian product which can be reliable and can be owned by all level of society. The operational planning is necessary before starting any business whether it is a business based on production or services. Besides administration and marketing, operation also plays an important role to ensure that the company meets the specification needed and achieves their goal. This operational activity includes the transformation of the business input through some process which is established to produce the output. Toy City Sdn. Bhd is a company based on selling and services business. In Toy City Sdn. Bhd. it provides a fully integrated repairing, modification and gives some tips about the controller. Unlike some repairing and modification, Toyz City is meant to make a new model that to improve the controller to become easier and efficient. In addition, it also give some tips to the customer or user of this toy how to make the car faster and to prevent the car from damaging.